Investigative analysis of clustering routing protocols for scalable sensor networks - Salami, A. F.; Anwar, Farhat; Aibinu, A. M.; Bello-Salau, H; Hassan Abdalla Hashim, Aisha (2011)
New advancements in the technology of wireless sensors have contributed to the development of special protocols which are unique to sensor networks where minimal energy consumption is vital and very important. As a result, the focus and effort of researchers is on designing better routing algorithms for a given application and network architecture of interest. Flat-based routing protocols have been found to be less advantageous to clustering routing protocols when their performance are compared in a large-scale wireless sensor network scenario. This is due to the fact that clustering operation reduces the amount of redundant messages that are transmitted all over the network when an event is detected. This paper is an investigation of cluster-based routing protocols for wireless sensor networks.